Electrospun Polymer Nanofibers for Food and Health Applications - Gizdavic-Nikolaidis, Marija (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The electrospinning method has the unique ability to produce structured polymeric fibers on the micro or nano scale and to generate novel materials for food and healthcare purposes. The potential of electrospun nanofibers for human healthcare applications is promising, for example, in tissue/organ repair and regeneration, in medical diagnostics and instrumentation, and as vectors to deliver drugs and therapeutics, as biocompatible and biodegradable medical implant devices, as protective fabrics against environmental and infectious agents in hospitals and general surroundings. Furthermore, considerable effort has been directed toward developing scaffolds using biodegradable and biocompatible synthetic, natural polymers or renewable materials that enhance in vitro cell growth, while killing pathogenic bacteria cells. This Special Issue ""Electrospun Polymer Nanofibers for Food and Health Applications" will cover the latest research of electrospun nanofibres in this field including shape-memory electrospun fibre meshes with programmable cell orientation, water-absorbing nano?ber meshes for e?cient removal of excess water from kidney failure patients, and hydrogel nano?bers which can be used as a drug carrier for methylene blue.